2016
DOI: 10.1097/md.0000000000002785
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Taxanes- and Oxaliplatin-Based Chemotherapy in the Treatment of Gastric Cancer After D2 Gastrectomy for Different Lauren Types

Abstract: To investigate the efficacy of Taxanes- and Oxaliplatin-based chemotherapies (TC and OC) in the treatment of gastric cancer patients after D2 gastrectomy with different Lauren types. In this study, 299 patients of gastric adenocarcinoma with D2 lymph node dissection were reviewed between 2007 and 2014. Chemotherapies were classified as Oxaliplatin-based and Taxanes-based regimen. Treatment outcomes were analyzed according to different Lauren types, such as the intestinal type, diffuse type, and mixed type grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Nevertheless, there has been conflicting result reported that in diffuse type gastric cancer; patients in the oxaliplatin-based chemotherapy group had a longer median DFS (47.0 months vs. 28.6 months, P = 0.04) and OS (51.9 months vs. 34.5 months, P = 0.048) compared with those in taxane-based chemotherapy group [22]. We believed that the possible reasons for these conflicting results might be the selection of enrolled patients and different adjuvant chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, there has been conflicting result reported that in diffuse type gastric cancer; patients in the oxaliplatin-based chemotherapy group had a longer median DFS (47.0 months vs. 28.6 months, P = 0.04) and OS (51.9 months vs. 34.5 months, P = 0.048) compared with those in taxane-based chemotherapy group [22]. We believed that the possible reasons for these conflicting results might be the selection of enrolled patients and different adjuvant chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study on adjuvant chemotherapy showed that a diffuse histological type might benefit from oxaliplatin-based chemotherapy, whereas an intestinal histological type might benefit from taxanebased chemotherapy. 16 A recent retrospective study showed that the overall response rate of PB regimens was higher than TB regimens, although this difference was not statistically significant. 8 XParTS-1 trial revealed safety, high response rate, and efficacy of XP.…”
Section: Discussionmentioning
confidence: 98%
“…Although OS was not significantly differentiated in each group, the risk factor of undifferentiated type was second‐line TB chemotherapy. A previous study on adjuvant chemotherapy showed that a diffuse histological type might benefit from oxaliplatin‐based chemotherapy, whereas an intestinal histological type might benefit from taxane‐based chemotherapy 16 . A recent retrospective study showed that the overall response rate of PB regimens was higher than TB regimens, although this difference was not statistically significant 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Histological types of GC mainly include the intestinal type of well-differentiated tubular and papillary adenocarcinoma, and the diffused type of low-differentiated adenocarcinoma and signet ring cell carcinoma [ 22 ]. It has been demonstrated that GC of different histological types responded differently to therapies and hence resulting in different outcomes [ 23 ]. The results of this study demonstrated that perfusion parameters were important indicators for LNM, tumor differentiation, and histological type in LAGC patients.…”
Section: Discussionmentioning
confidence: 99%